Insights to Skin-turf Friction as Investigated Using the Securisport - Tay, Sock Peng (2015)
The objective of this study was to investigate the effect of the infill and fibers of an artificial turf surface to the overall frictional behavior of the surface. The assessment was conducted using the Securisport test device in accordance to the FIFA Test Method so as to evaluate the effectiveness of the standard test in describing the frictional property of an artificial turf surface. Experiments showed that surfaces of varying infill depths and infill types produced characteristic features in their friction profiles that were a result of the fiber-infill interactions. The surface without infill exhibited the highest frictional values, with distinct peak and trough features. Surfaces completely filled with sand or rubber displayed similar profiles with relatively low frictional values. Test results showed that turf fibers influenced the frictional behaviour of partially-filled systems to a great extent. The results from the Securisport were useful in providing insights to how various turf components affect the skin-turf interaction and may be beneficial in the development of more skin-friendly turf products.